Analisis elemen hingga untuk siklus berjalan pada model prostetik lentur pergelangan kaki - Zakki Fuadi Emzain; Utsman Syah Amrullah; AM. Mufarrih (Politeknik Negeri Lhokseumawe, 2020)
The model of compliant prosthetic ankle-foot is proposed as an alternative prosthetic aid for people with disabilities to do activities. The model is designed and analyzed to determine its strength and feasibility before being fabricated. The two main stages in this research are model design and model analysis. The shape of the model was designed with several elastic cavities and arches using the concept of a compliant mechanism. Finite element analysis (FEA) was performed on the prosthetic model when the stance phase on the mechanism of the human gait cycle. Because the prosthetic foot area is in contact with the ground on this cycle phase. Three main positions in 0-64% of the gait cycle are heel strike, midstance, and toe-off positions used as boundary conditions. The amount of load given adjusts the bodyweight percentage of the gait cycle with a reference of 80 kg. The direction of loading was by following the angle of the foot when dorsiflexion to plantarflexion during the stance phase. The biggest deformation results occurred in the toe-off position with two peak cycles of 4.69 mm and 4.45 mm at 17% and 51% of the gait cycle. While the smallest deformation occurred in the midstance position with an average of 0.08 mm. Because it used fixed support with two pedestals on the soles of the prosthetic. Maximum stress occurred in the toe-off position of 16.45 MPa at 17% of the gait cycle. With a safety factor of 1.63, the value is still safe because it is below the yield strength value of ABS material. While the largest strain of energy was located in the lower area in the middle of the arch between the toe and sole foot in the toe-off position of 3.55 mJ.